A robust phase watermarking algorithm using conjugate symmetric sequency-ordered complex Hadamard transform - Aung, Aye (2011)
This paper presents a novel watermarking algorithm based on a newly developed transform known as conjugate symmetric sequency-ordered complex Hadamard transform (CSSCHT). The algorithm is performed in the sequency domain where the phases of the CS-SCHT coefficients are altered to convey the watermark information using the phase-shift-keying (PSK) modulation. The amplitude boost (AB) method is employed to improve the robustness of the watermarking scheme and the spread spectrum (SS) technique is adopted to increase the security of the watermark against various attacks. The robustness of the proposed scheme is investigated by various types of image attacking operations such as JPEG compression, resizing, cropping and low-pass filtering.